APLIKASI PENJUALAN TOKO IKAN HIAS MENGGUNAKAN PEMBAYARAN PAYMENT GATEWAY BERBASIS WEBSITE - Febrian, Faldi; Hidayat, Taufik; Windyasari, Vina Septiana (JURNAL TEKNIK INFORMATIKA UNIS, 2021)
Currently the ornamental fish selling system in Febrianbetta24 still uses a manual system, which only relies on word of mouth information from buyers to other buyers or still traditionally, which is still selling offline, by implementing an online sales system it will reach consumers more widely, especially in In the Tangerang city area, in a short time buyers do not need to visit the Febrianbetta24 waterfall shop. In a better and more efficient system sales, it is better to use an online shopping system to save time and provide comfort and convenience in buying ornamental fish products in stores and also for more efficient payment transactions, you should use credit card, so that consumers don't have to bother bringing cash especially with a large enough nominal, just bring a credit card for payment. With the online sales system application at the febrianbetta24 store, it can be easier to make accurate sales reports, previously every purchase in the store's sales report was not well coordinated. Applications help and support the sales system used to be difficult to know the number of products that are ready in the store. Now with this application, it is easier to see the available stock